Pemenuhan Hak Pendidikan Terhadap Anak Terlantar Kriteria Anak Yatim PiatuDi Yayasan Sosial Panti Asuhan Yatim Piatu Dan Terlantar Dharmo Yuwono - Mia Indah Puspita Sari; Wahyu Hariadi; Esti Ningrum (Wijayakusuma Law Review, 2023)
This study aims to find out how the implementation of the Dharmo Yuwono Orphanage and Abandoned SocialFoundation in fulfilling the right to education for neglected children is the criteria for orphans and to find outwhat obstacles or obstacles are faced and the efforts made by the Orphanage Social Foundation. And AbandonedDharmo Yuwono. Based on the results of the research and discussion, it can be concluded that the implementationof fulfilling the right to education for neglected children criteria for orphans at the Dharmo Yuwono Orphanageand Abandoned Social Foundation is in accordance with Article 31 paragraph (1) of the 1945 Constitution of theRepublic of Indonesia which states that every citizens have the right to education and Article 34 which states thatthe poor and neglected children are protected by the state, in accordance with Law Number 35 of 2014concerning Amendments to Law Number 23 of 2002 concerning Child Protection and Regulation of the Ministerof Social Affairs of the Republic Indonesia Number: 30/HUK/2011 which states that fulfilling the rights ofneglected children, one of which is the right to education, is carried out by providing formal, non-formal andinformal education. Obstacles in implementing the fulfillment of the right to education for neglected childrenaccording to the criteria for orphans at the Dharmo Yuwono Orphanage and Abandoned Social Foundation,namely the lack of awareness of foster children in carrying out their rights and obligations